Intrinsic Cholinergic Neurons in the Hippocampus: Fact or Artifact? - Blusztajn, Jan Krzysztof; Rinnofner, Jasmine (Frontiers in Synaptic Neuroscience, 2016)
It is generally agreed that hippocampal acetylcholine (ACh) is synthesized and released exclusively from the terminals of the long-axon afferents whose cell bodies reside in the medial septum and diagonal band. The search for intrinsic cholinergic neurons in the hippocampus has a long history; however evidence for the existence of these neurons has been inconsistent, with most investigators failing to detect them using in situ hybridization or immunohistochemical staining of the cholinergic markers, choline acetyltransferase (CHAT) or vesicular acetylcholine transporter (VACHT). Advances in the use of bacterial artificial chromosome (BAC) transgenic mice expressing a reporter protein under the control of the genomic elements of the Chat gene (Chat-BAC mice) have facilitated studies of cholinergic neurons. Such mice show robust and faithful expression of the reporter proteins in all known cholinergic cell populations. The availability of the Chat-BAC mice re-ignited interest in hippocampal cholinergic interneurons, because a small number of such reporter-expressing cells is frequently observed in the hippocampus of these mice. However, to date, attempts to confirm that these neurons co-express the endogenous cholinergic markers CHAT or VACHT, or release ACh, have been unsuccessful. Without such confirmatory evidence it is best to conclude that there are no cholinergic neurons in the hippocampus. Similar considerations apply to other BAC transgenic lines, whose utility as a discovery tool for cell populations heretofore not known to express the genes of interest encoded by the BACs, must be validated by methods that detect expression of the endogenous genes.